Summertime Oxygen Depletion and Acidification in Bohai Sea, China - Song, Guisheng; Zhao, Liang; Chai, Fei; Liu, Fangfang; Li, Mengting; Xie, Huixiang (Frontiers in Marine Science, 2020)
Increasing attention has recently been drawn to oxygen depletion and ocean acidification in coastal seas and their impacts on the marine ecosystem. Intensive organic matter degradation combined with weak water exchange is considered to be mainly responsible for bottom water oxygen depletion and acidification. Hypoxia and acidification in the bottom water of Bohai Sea have been frequently observed in summer seasons over the past decade. In this study, monthly surveys were conducted along an inshore-offshore transect in the north Bohai Sea from May to August in 2017 and 2018. The physical structure of the water column in the study area was characterized by a well-mixed surface layer and an essentially homogeneous deep layer that were separated by a strong pycnocline over the period from mid-Jun to late August in both years. Dissolved oxygen (DO), pH and dissolved inorganic carbon (DIC) in the water column were also split into two layers by the pycnocline and varied little in each layer. No significant interannual variations were observed for the temporal progressions of DO, pH and DIC in the bottom water. Average DO concentration and pH in the bottom water linearly decreased with time from May to August while DIC presented an opposite trend. DO became increasingly unsaturated from mid-June to late August when DO decreased to 96 µmol L -1 and pH to 7.74. The molar ratio of net oxygen consumption to DIC production was 1.42, similar to the Redfield ratio (1.30). Pelagic respiration (> 60%) linked to degradation of fresh organic matter prevailed over sediment respiration (< 40%) in contributing to the oxygen depletion and acidification observed in this shallow water body. The duration and intensity of oxygen depletion and acidification in the study area were strongly affected by stormy weather events such as typhoons.